WEB BASED CLASSROOM SYSTEM - Tejashree Gurav (International Journal of Innovations in Engineering Research and Technology, 2021)
One of the changes that the "Information Age" has brought to classrooms is that a Web-Based Classroom Management Support System (WBC) is now required for more efficient classroom management in elementary schools. This research aims at finding desirable Internet uses for more efficient classroom management through designing and implementing a web-based classroom support system. It has been possible to support classroom management beyond the limits of time and space with content found on the web and through guiding learners’ internet usage in educational directions utilizing the resources on the web in more academic ways, and when applied in classrooms to help direct learners’ active participation developing each learners’ own special abilities and aptitudes. A WBC system is expected to offer upgraded classroom management